مشكلات قراءة اللغة العربية لغير ناطقين بها وسبيل ازالتها - Nurfin Sihotang (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2019)
This is paper explain the problem  reading text in arabic for who is  not Arabic his mother tongue, the arabic text as another language onsists from the vocal, morphen, syntax and semantic, bi side of that language need skill  listening, speaking, writing and reading, all of this have related to each other        The  problem of reading in arabic text a special for who not arabic his mother tongue, back to the tructur of arabic language  from the problem reading vocal, reading morphen  and reanding semantic            To the solve of that  reading prolem in arabic test the student must know and understoot  the correct speling of arabic from the vocal, morphen, syntax and semantics and the student and teacher must readyto learnd step by step and to repeat of the lesson reading